CircSKA3 acts as a sponge of miR‐6796‐5p to be associated with outcomes of ischemic stroke by regulating matrix metalloproteinase 9 expression. (10th November 2021) - Xu, Tian; Li, Yuqing; Zhu, Ning; Su, Yuanyuan; Li, Junrui; Ke, Kaifu
Abstract: Background and purpose: This study was undertaken to screen the circular RNAs (circRNAs) influencing matrix metalloproteinase 9 (MMP9) through the competing endogenous RNA (ceRNA) network and evaluate the prognostic value of these circRNAs for acute ischemic stroke. Methods: A total of 220 ischemic stroke patients and 62 healthy subjects were included in this study. RNA was isolated from blood collected in PAXgene tubes. Illumina sequencing, quantitative real‐time polymerase chain reaction (qRT‐PCR) validation, and luciferase reporter assay were explored to construct and verify the existence of a circRNA–microRNA (miRNA)–matrix metalloproteinase–9 (MMP9) network. The 215 ischemic stroke patients were recruited in a prognostic cohort. They were prospectively followed up for 3 months after stroke onset, and a poor functional outcome was defined as a major disability or death. Results: After Illumina sequencing, six circRNAs were predicted to bind miRNAs and then regulate MMP9 messenger RNA (mRNA). qRT‐PCR showed that only circSKA3 was significantly increased in ischemic stroke patients compared to healthy controls and positively associated with MMP9 mRNA expression. Luciferase reporter assay further verified a direct interaction between circSKA3, MMP9, and hsa‐miR‐6796‐5p. Patients in the top tertile of circSKA3 had a 2.672‐fold ( p < 0.05) risk of poor functional outcome, compared with those in the bottom tertile ( p for trend = 0.016). The outcome was predicted by circSKA3 with area under the receiver operating characteristic curve at 0.614 ( p = 0.004). Conclusions: circSKA3 functioned as a ceRNA for hsa‐miR‐6796‐5p to aggravate the progression of ischemic stroke via targeting MMP9. Baseline circSKA3 was positively associated with poor outcomes of ischemic stroke. circSKA3 may be a potential biomarker or therapeutic target in ischemic stroke. Abstract : circSKA3 was increased in patients with acute ischemic stroke compared with healthy controls. In addition, circSKA3 was also positively associated with poor clinical outcome of ischemic stroke. The mechanism may be that it functioned as a competing endogenous RNA for hsa‐miR‐6796‐5p via targeting matrix metalloproteinase 9.